Buddhism and Nature Conservation: An Insight from the Pali Tipitaka (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
Humanity relies on nature for essential resources such as food, shelter, and medicine. However, excessive exploitation driven by consumerism and greed has led to severe environmental crises. Buddhism, with its emphasis on ethics and mindfulness, provides valuable insights into environmental conservation. Although the Buddha did not explicitly address pollution, early Buddhist texts in the Pāli Tipiṭaka highlight the deep connection between human morality and nature. The Aggañña Sutta illustrates how moral decline leads to environmental degradation, while the Cakkavattisihanāda Sutta warns of the dangers of excessive greed. Fundamental Buddhist principles, such as impermanence (aniccā) and the five natural laws (pañca niyāmadhammā), emphasize the relationship between moral actions and natural processes. The teachings of contentment (santutthī) and non-violence (ahiṁsā) further encourage a respectful and sustainable relationship with nature. The Pāli canon also stresses the importance of flora and fauna. The Five Precepts advocate compassion towards animals and plants, while the Karaniyamettā Sutta promotes loving-kindness (mettā) toward all beings. Buddhist scriptures, including the Dhammapada and Simsapā Sutta, use nature-based similes to reinforce environmental ethics. Buddhist monastic discipline strictly prohibits harming plants and animals, advocating for a sustainable lifestyle. The Vinaya Piṭaka emphasizes environmental purity, including water conservation. Furthermore, Buddhist governance, as outlined in the Dasarāja Dhamma, advises rulers to protect nature through ethical stewardship. Buddhist teachings on contentment, mindfulness, and frugality, as seen in the Raṭṭhapãla Sutta and Mettā Sutta, promote sustainable living practices. This research explores how Buddhist ethical principles can be applied to contemporary environmental challenges. Industrialization and unchecked consumption have resulted in environmental degradation, but Buddhist teachings offer a framework for sustainability based on mindfulness and ethical responsibility. By analyzing key texts such as the Aggañña Sutta and Cakkavattisihanāda Sutta, this study aims to highlight the link between moral values and ecological well-being. Additionally, it will examine the role of the Five Precepts, Karaniyamettā Sutta, and monastic regulations in promoting conservation. Integrating Buddhist ethical principles into modern environmental efforts can lead to a more sustainable and compassionate approach to nature. The research seeks to demonstrate how Buddhist teachings can inspire environmentally responsible lifestyles, policy-making, and governance. With its emphasis on interconnectedness, moderation, and respect for life, Buddhism provides a profound ethical foundation for addressing today’s ecological crises.